Corrosion behaviour of twin-roll cast 8006 aluminium alloy foil with different thicknesses for the food packaging industry - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2021)
Purpose The purpose of this paper is to investigate and find out the surface and electrochemical behaviours of twin roll cast (TRC) 8006 aluminium alloy with different thicknesses due to the cold rolling rates after the TRC process. Design/methodology/approach The 8006 aluminium alloys are mostly used for the food packaging industry, as they are corrosion resistant, lightweight and shapable materials. The present work investigates the surface and corrosion behaviours of 8006 aluminium alloys at different thicknesses. TRC aluminium alloys were cold-rolled at two different reduction rates before investigation. X-ray diffraction (XRD) and energy dispersive spectroscopy (EDX) tests were used to examine the phase and elemental analyses. FE-SEM and 3D profilometry also used to observe surface morphology. Open circuit potential (OCP), potentiodynamic polarization and electrochemical impedance spectroscopy tests (EIS) were carried out to find out corrosion behaviours. The results show that the more cold rolling reduction (CRR), the more corrosion rate and surface affection of the TRC 8006 aluminium alloys. Findings According to the electrochemical tests (OCP, potentiodynamic polarization test and EIS) and surface morphology results (such as SEM, 3D profilometry and XRD) the more the rolling rate the less the corrosion resistance. Originality/value First corrosion behaviour investigation of twin-rolled 8006 Al alloys using electrochemical techniques. First investigation of CRR effects on electrochemical corrosion behaviour of 8006 Al alloys with 3.5 wt.% NaCl solution using EIS. First investigation of 8006 Al alloys as a food packaging material with electrochemical ways.
Keywords: 8006 Al alloy; OCP; Potentiodynamic polarization; EIS; XRD; Food packaging